6q22.33 microdeletion in a family with intellectual disability, variable major anomalies, and behavioral abnormalities. (3rd September 2015) - Mackenroth, Luisa; Hackmann, Karl; Beyer, Anke; Schallner, Jens; Novotna, Barbara; Klink, Barbara; Schröck, Evelin; Di Donato, Nataliya
<x xml:space="preserve">Abstract</x> Interstitial deletions on the long arm of chromosome six have been described for several regions including 6q16, 6q22.1, and 6q21q22.1, and with variable phenotypes such as intellectual disability/developmental delay, growth retardation, major and minor facial anomalies. However, an isolated microdeletion of the sub‐band 6q22.33 has not been reported so far and thus, no information about the specific phenotype associated with such a copy number variant is available. Here, we define the clinical picture of an isolated 6q22.33 microdeletion based on the phenotype of six members of one family with loss of approximately 1 Mb in this region. Main clinical features include mild intellectual disability and behavioral abnormalities as well as microcephaly, heart defect, and cleft lip and palate. © 2015 Wiley Periodicals, Inc.